Trained immunity-related vaccines: innate immune memory and heterologous protection against infections - Ziogas, Athanasios; Netea, Mihai G. (Trends in molecular medicine, 2022)
The innate immune system is able to build memory-like features in response to certain infections or vaccines, resulting in enhanced responsiveness upon (re)challenge with the same or an unrelated pathogen, a phenomenon termed ‘trained immunity’. Compared with antigen-dependent adaptive immune responses triggered by classical vaccines against specific pathogens, trained immunity-related vaccines induce enhanced innate immune responses against unrelated pathogens and provide ‘heterologous protection’. Here, we discuss the heterologous effects of vaccines against infections and detail the latest insights into the cellular and molecular mechanisms mediating trained immunity. Additionally, novel vaccine strategies are suggested for fighting new pandemics in the future by taking advantage of the heterologous memory features of trained immunity. Trained innate immune cells have improved antimicrobial function mediated by transcriptional and epigenetic rewiring. Long-lasting trained immunity is centrally regulated in hematopoietic progenitors in the bone marrow and peripherally induced in tissue-resident cells.Distinct trained immunity programs at the single cell level identify trained monocyte subpopulations.Heterologous or nonspecific protection of vaccines against unrelated pathogens can be partially explained by induction of trained immunity responses.BCG, MTBVAC, influenza, measles, and possibly the new mRNA Coronavirus 2019 (COVID-19) vaccines induce trained immunity signatures, while trained immunity inducers can act as vaccine adjuvants.Environmental factors, the microbiome, circadian rhythm, genetics, and sex influence vaccine-induced trained immunity heterogeneity.